Microglial Ultrastructure in the Hippocampus of a Lipopolysaccharide-Induced Sickness Mouse Model - Savage, Julie C.; St-Pierre, Marie-Kim; Hui, Chin Wai; Tremblay, Marie-Eve (Frontiers in Neuroscience, 2019)
Sickness behavior is a set of behavioral changes induced by infections and mediated by pro-inflammatory cytokines. It is characterized by fatigue, decreased appetite and weight loss, changes in sleep patterns, cognitive functions, and lost interest in social activity. It can expedite recovery by conserving energy to mount an immune response involving innate immunity. To provide insights into microglial implication in sickness behavior with special focus on cognitive and social impairment, we investigated changes in their ultrastructure and interactions with synapses using a toxemia mouse model. Adult mice were injected with 1 mg/kg lipopolysaccharide (LPS) or saline, and assayed for signs of sickness behavior. LPS treated mice displayed reduced activity in open-field tests 24 h post-injection, while social avoidance and weight gain/loss were not significantly different between treatment groups. Microglia were investigated using electron microscopy to describe changes in their structure and function at nanoscale resolution. Microglial cell bodies and processes were investigated in the hippocampus CA1, a region responsible for learning and memory that is often impacted after peripheral LPS administration. Microglia in LPS treated animals displayed larger cell bodies as well as less complex processes at the time point examined. Strikingly, microglial processes in LPS injected animals were also more likely to contact excitatory synapses and contained more phagocytic material compared with saline injected controls. We have identified at the ultrastructural level significant changes in microglia-synapse interactions shortly after LPS administration, which draws attention to studying the roles of microglia in synaptic rewiring after inflammatory stimuli.